ISLAMIC BANKING PERFORMANCE, FINANCIAL INCLUSION, AND HUMAN DEVELOPMENT: EVIDENCE FROM PROVINCIAL ISLAMIC BANKING IN INDONESIA - Maddani Akhsa Nulyani; Nurfitri Harkunti Kemala Hayati; Amelia Fitri Harahap; Fadiyah Aulannisa; Nisfi Nuur Lailatin (UIN Sunan Gunung Djati Bandung, 2025)
Islamic banking, founded on unique ethical principles, is increasingly acknowledged as a key driver of sustainable development. This study explores the relationship between Islamic banking performance, financial inclusion, and the Human Development Index (HDI) in Indonesia. Employing quantitative methods, panel data from 33 provinces spanning 2016, 2019, and 2022 were obtained from the Financial Services Authority (OJK) and the Central Statistics Agency (BPS). Path analysis was conducted using STATA 17 to investigate the direct and indirect effects of Islamic banking performance on HDI, with financial inclusion as a mediating variable. Findings reveal that bank size, as a performance indicator, negatively impacts HDI directly, and this adverse effect is intensified through financial inclusion. Conversely, Third-Party Funds (TPF) exhibit a positive direct association with HDI, also mediated by financial inclusion, highlighting the importance of accessible financial resources in enhancing human development. These findings suggest Islamic banking can support sustainable development by enhancing human development, especially when financial inclusion is prioritized. Policymakers and Islamic financial institutions should focus on expanding financial access to marginalized groups, and to innovate products tailored to their needs. This study contributes valuable insights into optimizing Islamic banking’s role in achieving broader socio-economic goals in Indonesia.